Solanum betaceum (Terong Belanda): Buah Asli India yang Kaya Antioksidan: Solanum betaceum (Tamarillo): A Potential Antioxidant Rich Indigenous Fruit of India - Arivazhagan, Suganya; Kalpana, Chinnappan A (Universitas Airlangga, 2025)
Background: Solanum betaceum, commonly known as tamarillo, a nutritious fruit rich in vitamin C, dietary fibre, and an essential antioxidant that protects cells from free radical damage, contributing to overall health. Objectives: The study aimed to achieve the confirmation of antioxidant activity of fruit followed by functional group and components identification. Methods: Fiber content was determined enzymatically. Phytochemicals were screened using polar solvent extracts, with Gas Chromatography-Mass Spectrometry identifying metabolites and Fourier Transform Infrared Spectroscopy characterizing secondary metabolites. Antioxidant capacity was measured by DPPH (2,2-diphenyl-1-picrylhydrazyl) assay. Results: Fresh tamarillo fruit exhibited a high content of dietary fiber (47.3 g/100 g), Vitamin C (27 mg/100 g), and β-carotene (832 mcg/100 g) the major nutrients accounts for the antioxidant. Phytochemical screening revealed the highest abundance of phenolic compounds, flavonoids, terpenoids, and quinones in the methanol extracts. Identification of functional groups used to confirm the presence of bioactive components: OHalcoholic/phenolic (3300-2900 cm-1), C=Caromatic(1600-1450cm-1), C-Haromatic(680-470 cm-1). with Gas Chromatography-Mass Spectrometry analysis identified various metabolic components, including beta-Bisabolene, Hexadecanoic acid methyl ester, Palmitic acid, Pentadecanecarboxylic acid, Heneicosane, Eicosane, Dotriacontane, Myrtenyl formate, and Isobutyric acid. The DPPH free radical scavenging assay demonstrated tamarillo fruit’s potent antioxidant activity, with an IC50 value of (22.1 µg/mg mL⁻¹) significantly lower than the control (p-value<0.001). Conclusions: These findings revealed a broad spectrum of beneficial properties in tamarillo. Presence of vitamin C and dietary fibre confirms the antioxidant activity and it makes tamarillo a promising fruit for the prevention of cancer and other degenerative diseases.